2022
DOI: 10.1177/10732748221084853
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model of Early Death of Resectable Pancreatic Ductal Adenocarcinoma After Curative Resection: A SEER-Based Study

Abstract: Objective This study aims to determine the factors that predict early death and establish a predictive model for early death by analyzing clinical characteristics of patients with resectable pancreatic ductal adenocarcinoma (R-PDAC) who die early after radical surgery. Materials and Methods This was a retrospective study of patients who underwent radical surgical resection for R-PDAC in the Surveillance, Epidemiology, and End Results (SEER) database. Patients with overall survival ≤ 12 months were assigned as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…To date, it is one of the few works with the largest amount of sample size that made cut-off points in the values of the predictors, establishing a prediction model with the aforementioned variables. [11] Analyzing the rest of the bibliography, we can see that this cut-off point for the tumor marker varies signi cantly between the different reference centers and there is no clear correlation in the cut-off value. The Japanese group of Imamura establishes a cutoff point of ca 19 − 9 of (> 52 U/mL) preoperative and (> 37 U/mL) postoperative.…”
Section: Discussionmentioning
confidence: 98%
“…To date, it is one of the few works with the largest amount of sample size that made cut-off points in the values of the predictors, establishing a prediction model with the aforementioned variables. [11] Analyzing the rest of the bibliography, we can see that this cut-off point for the tumor marker varies signi cantly between the different reference centers and there is no clear correlation in the cut-off value. The Japanese group of Imamura establishes a cutoff point of ca 19 − 9 of (> 52 U/mL) preoperative and (> 37 U/mL) postoperative.…”
Section: Discussionmentioning
confidence: 98%
“…Then we evaluated the accuracy to predict early recurrence rate for pancreatic cancer based on the HM-CTCs counts. Our team previously reported a multicenter retrospective study in which 9 months was the best threshold to distinguish early from late recurrence ( 53 ). We observed that the AUC of HM-CTCs in PB for distinguishing early recurrence was 0.787, and the accuracy significantly increased when we tested the AUC of PVB HM-CTCs (0.825).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, predicting the oncological outcomes of this disease based on the prognostic factors plays a crucial role in increasing PC survival by detecting the factors contributing to worsening the patients’ outcomes at earlier stages [ 15 ]. More specifically, early prediction of the mortality risk of PC based on these factors can significantly increase PC survival by modifying these factors at earlier stages [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%